Information Doesn't Want to Be Free: Laws for the Internet Age - Doctorow, Cory; Gaiman, Neil; Palmer, Amanda (McSweeney's, 2014)
Filled with wisdom and thought experiments and things that will mess with your mind." Neil Gaiman, author of The Graveyard Book and American Gods In sharply argued, fast-moving chapters, Cory Doctorow's Information Doesn't Want to Be Free takes on the state of copyright and creative success in the digital age. Can small artists still thrive in the Internet era? Can giant record labels avoid alienating their audiences? This is a book about the pitfalls and the opportunities that creative industries (and individuals) are confronting today about how the old models have failed or found new footing, and about what might soon replace them. An essential read for anyone with a stake in the future of the arts, Information Doesn't Want to Be Free offers a vivid guide to the ways creativity and the Internet interact today, and to what might be coming next. This book is DRM-free.